Cost-effectiveness Analysis of a Pre-exposure Prophylaxis (PrEP) Programme in Ireland - Hayes, Catherine (My University, 2021)
Objectives: To estimate the cost-effectiveness of introducing a publicly funded pre-exposure prophylaxis (PrEP) program in Ireland. Methods: We constructed a state-transition Markov model. This was a cross-sectional population model that tracked all HIV-negative men who have sex with men (MSM) in Ireland over their lifetime. Access to a publicly funded PrEP program (medications + frequent monitoring) in high-risk MSM was compared with no PrEP. The primary outcome measure was the incremental cost-effectiveness ratio (ICER). Results: In the base case, introducing a PrEP program was considered cost saving and provided significant health benefits to the population. Univariate sensitivity analysis demonstrated that PrEP efficacy and HIV incidence had the greatest impact on cost-effectiveness. Including an increase in sexually transmitted infections had a negligible impact on the results. Efficacy was a significant driver in the model. PrEP was cost saving at all efficacy values above 60%, and at the lowest reported efficacy in MSM (44% in the iPrEX trial), the ICER was €4711/QALY (highly cost-effective). Event-based dosing (administration during high-risk periods only) was associated with additional cost savings. We estimated that 1705 individuals (95% CI: 617-3452) would join the program in year 1. The incremental budget impact was €1.5m (95% CI: €0.5m to €3m) in the first year and €5.4m over 5 years (95% CI: €1.8m to €11.5m), with 173 cases of HIV averted over 5 years. Conclusion: We found that the introduction of a PrEP program would be considered cost saving in the first cost-effectiveness analysis of its kind in Ireland.
PUBLISHED
Keywords: Cost-effectiveness analysis; HIV prevention; Pre-exposure prophylaxis; PrEP; Inclusive Society; Economics of health service provision; HEALTH ECONOMICS; Medicine; Public health